2021
DOI: 10.1108/bpmj-12-2020-0580
|View full text |Cite
|
Sign up to set email alerts
|

Components to foster organizational resilience in tourism SMEs

Abstract: PurposeSmall- and medium-sized enterprises (SMEs) mainly rely on their structure and internal networks to achieve their goals and remain competitive. However, their limited internal capabilities and complex environments can hinder their stability. Thus, this study evaluated the relationships among specific factors toward fostering organizational resilience (OR) in tourism SMEs.Design/methodology/approachA multi-methodological approach was adopted to address this research study, including (1) social network ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 83 publications
1
20
0
Order By: Relevance
“…In this regard, Figueiredo et al. (2020) and Nunez-Rıos et al . (2022) mentioned that SMEs face certain problems such as poor planning and management processes, a lack of clear purpose, inadequate staff training and inconsistent relationships between operating units and their management and control systems.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 96%
See 3 more Smart Citations
“…In this regard, Figueiredo et al. (2020) and Nunez-Rıos et al . (2022) mentioned that SMEs face certain problems such as poor planning and management processes, a lack of clear purpose, inadequate staff training and inconsistent relationships between operating units and their management and control systems.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 96%
“…bouncing back from an unpredictable occurrence such as an economic crisis (Akg€ un and Keskin, 2014;Tognazzo et al, 2016). In order to maintain their competitiveness, SMEs mainly rely on their organizational structure, their employees' engagement and the proper implementation of management approaches because of their limited configuration and access to resources (Nunez-Rıos et al, 2022). In this regard, Figueiredo et al (2020) and Nunez-Rıos et al (2022) mentioned that SMEs face certain problems such as poor planning and management processes, a lack of clear purpose, inadequate staff training and inconsistent relationships between operating units and their management and control systems.…”
Section: Crr 42mentioning
confidence: 99%
See 2 more Smart Citations
“…This research aimed to explore how tourism SMEs in the tourism supply chain use cloudenabled was increasing the online consumption value of tourists through e-marketplace systems (EMSs). Prior research has indicated that tourism has provided tourists with valuable travel-related information services tailored to their individual needs and locations online (Du et al, 2019;Nunez-Rios et al, 2022). From the TOE perspective, when tourists search for travel information with practical mobile application support (Shi and Tsai, 2020), their satisfaction with the brand and consumption will increase.…”
Section: Introductionmentioning
confidence: 99%